Management of Organic California Papaya (Carica Papaya L.) Cultivation in Tial Village, Salahutu District, Central Maluku Regency - Marasabessy, Dessy Ariyani; Lesilolo, Marthini Kristina (Fakultas Pertanian Universitas Darussalam Ambon, 2024)
Papaya ((Carica papaya L.) is one of the leading fruit commodities that are strategic to meet most of the food needs of the Indonesian people. The research aims to obtain nformation on the management of organic California papaya cultivation in Tial Village, Salahutu District, Central Maluku Regency. The research was conducted from October to November 2020 and used a survey method. Direct observations and interviews were conducted with farmers who cultivate the California papaya plant. The samples were taken as many as 15 heads of household farmers who cultivate organic California papaya. The results showed that the land ownership in the research location was their own and the land topography was flat to wavy. Overall, the organic California papaya farmers at the research location apply the concept of organic agricultural cultivation the The production of organic California papaya fruit in Tial Village reaches 100-130 kg of trees.